A synthesis of cephalostatin 1. Issue 12 (22nd March 2019) - Shi, Yong; Xiao, Qing; Lan, Quan; Wang, Da-Hai; Jia, Lan-Qi; Tang, Xiao-Hu; Zhou, Tao; Li, Min; Tian, Wei-Sheng
Abstract: A synthesis of cephalostatin 1 from hecogenin is described in detail. The gram-scale synthesis of south part features a Baeyer–Villiger oxidation of hecogenin to 16, 20-diol, a selective oxidation of C16OH with Dess–Martin periodinane, a Rh(I)-catalyzed C15C16 double bond shift to C14C15 position, and a Hg(OAc)2 -mediated spiroketal formation from cyclic enol ethers with alkenyl side chain at 2-position. Key transformations in the synthesis of north part, also on gram scale, include an abnormal Baeyer–Villiger oxidation of hecogenin to the corresponding dinorcholanic lactone, where a catalytic amount of iodine acts as a traceless and catalytic switch, an umpolung of steroidal 22-aldehyde to forge C22C23 bond with good stereochemical control, a cascade spiroketal-forming process to establish DEF rings in one operation, and a selective oxidation of C3OH. There are also other noteworthy transformations that, although not used in our final route, are valuable and could be applied to other syntheses, including: intra- or intermolecular SN 2′ processes of C14-heteroatom-substituted C15C16 alkenes, an unprecedented rearrangement of β-adduct of D-ring dienes and singlet oxygen, a chelation-controlled methylallylation of C23 aldehyde, and so on. Graphical abstract: Image 1 Highlights: Mercuric acetate promotes cyclic enol ethers with alkenyl chain at 2-position to form spiroketals. Iodide-catalyzed abnormal Baeyer-Villiger oxidation of steroidal sapogenin delivered dinorcholanic lactone. β-Adduct of D-ring diene with singlet oxygen rearranged to an unprecedented tricyclic structure. With a leaving group at C14, C15C16 double bond undergoes SN 2′ reaction inter- or intramolecularly. Both spiroketals of cephalostatin 1 are thermodynamically favorable.